The hidden harms of prison life for people with learning disabilities - Gormley, Caitlin (The British journal of criminology, 2022)
People with learning disabilities’ experiences of punishment and prison life remain invisible within prison policy and research. With participants’ voices central, this paper makes visible the hidden harms experienced by a hidden population, exposing the multi-faceted and nested forms of harm that people with learning disabilities encounter while in prison as a result of direct and indirect discrimination. It highlights the ways in which they navigate prison life and respond to structural and inaccessible barriers that adversely impact their understanding of their sentence, access to services, and ontological security. By drawing together conceptual and methodological insights from disability studies and prison sociology, I offer new insights into the distinct yet challenging aspects of prison life for people with learning disabilities.